A flow visualization of undulatory underwater swimming - A pilot study of three dimensional analysis - Shimojo, H.; Murakawa, R.; Sengoku, Y.; Sakakibara, J.; Tsubakimoto, S.; Takagi, H. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The purpose of this study was to visualize the flow characteristic behind a swimmer during undulatory underwater swimming (UUS). A male college swimmer performed dolphin kicks in a water flume channel (flow velocity was set at 0.8 m/s). By using the stereo PIV system, we captured the flow vector field in cross-sectional areas behind the swimmer and the swimmer's motions with a synchronized motion capture system. The vector fields were averaged for each kicking phase, and for spatial cross-sectional plane. This enabled visualization of the three dimensional flow field in UUS. The results showed that the swimmer created a counter vortex pair around the feet before the downward kid, and this appeared to assist the generation of thrust during the down kick motion.